Gaging consumer demand and preference for peeled, packaged, and labeled cooking bananas in Uganda - Kikulwe, Enoch Mutebi; Asindu, Marsy; Mulumba, Nasser; Mbabazi, Gloria; Ajambo, Susan (Bioversity International, 2021)
Cooking banana is widely grown and consumed the world over due to its distinct aroma and taste. It also forms the economic lifeline for many countries. However, the fruit is highly perishable owing to its high-water content, disease susceptibility and quick ripening after harvest. This results in significant economic losses across its marketing chain. A breakthrough towards reduction of the bulk of the losses incurred, especially at the retail level, has been achieved through a technological innovation that extends the shelf-life of fresh cooking banana in peeled and packaged form. However, consumer preference and demand for this novel product remains widely unknown. Our study therefore investigated consumer demand and preference for peeled banana products with varied attribute levels in two major banana consuming cities of Uganda—Kampala and Jinja. A Discrete Choice Experiment (DCE) was conducted with 360 banana consumers who were randomly picked using a systematic sampling approach from 8 banana retail markets located within the two sample cities. Principal factor analysis, based on perceptions and attitudes towards peeled banana products, was conducted to segment the respondents into market niches. Then, a latent class model (LCM) was estimated to identify the different segments for peeled banana products and the values they derive from the different products. Lastly willingness to pay (WTP) estimates for the different customer segments for peeled banana products with varied attribute levels was also determined.